The clinical value of glycosylated hemoglobin level in newly diagnosed ketosis-prone type 2 diabetes - Min, Rui; Xu, Yancheng; Peng, Bocheng (Frontiers in Endocrinology, 2023)
Objective To evaluate the clinical value of glycosylated hemoglobin (HbA1c) in newly diagnosed KPD. Methods A total of 330 patients with newly T2DM hospitalized in our department with an average age of 48.72±13.07 years years old were selected and divided into T2DM group (193 cases) and KPD group (137 cases). According to the quartile level of HbA1c, they were divided into group A (HbA1c < 8.90%, 84 cases), group B (8.90%≤HbA1c < 10.70%, 86 cases), group C (10.70% ≤ HbA1c ≤ 12.40%, 85 cases) and group D (HbA1c > 12.40%, 75 cases). The general clinical features, laboratory indicators and islet function of each group were compared. Spearman correlation analysis was used to explore the correlation between HbA1c and β-Hydroxybutyric acid (β-HB) and islet function.ROC curve was used to analyze the sensitivity and specificity of HbA1c in diagnosing KPD, and the optimal tangent point was obtained. Results HbA1c, β-HB, FFA, RBG, insulin dosage, GSP, OGTT (0, 0.5, 1, 2, 3h) in KPD group were significantly higher than those in T2DM group (P< 0.001). HDL-C, IRT (0, 0.5, 1, 2, 3h), HOMA-β , HOMA-IR, HOMA-IS, ΔC30/ΔG30, AUC insulin were significantly lower than those in T2DM group (P< 0.001). With the increase of HbA1c level, the incidence of ketosis , β-HB, FFA and insulin dosage increased, while IRT (0, 0.5, 1, 2, 3h), ΔC30/ΔG30, AUC insulin , HOMA-β and HOMA-IS decreased accordingly (P< 0.001). Spearman correlation analysis showed that HbA1c was positively correlated with β-HB (r=0.539, P < 0.001), and was negatively correlated with HOMA-β (r=-0.564, P < 0.001), HOMA-IS (r=-0.517, P < 0.01, P < 0.001), HOMA-IR (r=-0.177, P < 0.001), Δ C30/ Δ G30 (r=-0.427, P < 0.01) and AUC insulin (r=-0.581, P < 0.001). In ROC curve analysis, the optimal threshold for the diagnosis of KPD was 10.15%, . Conclusion In newly diagnosed T2DM patients, if HbA1c > 10.15%, it is more likely to develop KPD. Monitoring HbA1c level is conducive to timely detection of high-risk individuals with KPD and taking appropriate measures to prevent the occurrence and development of the disease.